1994
DOI: 10.1103/physrevlett.73.1857
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Charge Dynamics in a Doped One-Dimensional Transition Metal Oxide

Abstract: We have measured the electrical resistivity, polarized x-ray absorption, and magnetic neutron scattering for Y~"Ca,BaNi 1,zn, 05 to determine how doping affects the charge and spin dynamics of a Haldane chain compound. While Zn doping, which severs the NiO chains, increases the resistivity beyond that of the pure material, Ca doping introduces holes, residing mainly in the 2p, orbital of the oxygens in the NiO chains. Both dopants lead to simple finite size effects above the Haldane gap. In addition, we have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
139
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 26 publications
14
139
0
Order By: Relevance
“…But a lot of researches have shown that there is a spin gap in the excitation spectrum [10,11]. This result is now well supported by numerical calculations on spin-1 1D HAFM ring.…”
Section:   supporting
confidence: 68%
“…But a lot of researches have shown that there is a spin gap in the excitation spectrum [10,11]. This result is now well supported by numerical calculations on spin-1 1D HAFM ring.…”
Section:   supporting
confidence: 68%
“…[4][5][6][7][8][9] Many low-energy features of the model can be understood using an approximate mapping onto the nonlinear model (NL M). In particular, the low-lying excited states are constructed from a triplet of interacting bosons ͑magnons͒.…”
Section: Introductionmentioning
confidence: 99%
“…In another approach dynamics was provided to the holes [6] but the Ni-Ni exchange J was assumed larger than both the hole hopping amplitude and the short-bond NiO exchange. While studying these limits is instructive since gap states are produced, the drastic reduction in ρ dc observed experimentally upon doping [4] suggests that holes are likely mobile over several lattice spacings. [7] Thus, in this paper we propose a new model for Y 2−x Ca x BaNiO 5 with fully mobile S=1/2 holes interacting with S=1 spins, which is studied using realistic values for the couplings.…”
mentioning
confidence: 99%
“…Two remarkable experimental features were observed upon doping, namely (i) the reduction of the resistivity ρ dc by several orders of magnitude leading to a one dimensional conductor, and (ii) the creation of states inside the Haldane gap as revealed by inelastic neutron scattering (INS) data. [4] To understand these in-gap states, spin systems with site or bond impurities have been recently proposed. [5] Holes are assumed to be so strongly localized that their mobility is neglected.…”
mentioning
confidence: 99%